2012
DOI: 10.1097/brs.0b013e318221e859
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is Activated in Injured Neurons and Inhibited by Methylprednisolone After Experimental Spinal Cord Injury

Abstract: Through observing the enhanced autophagy expression in neurons soon after contusion injury and the inhibitive effect of methylprednisolone treatment, this study demonstrates the characteristics of autophagy expression after SCI and suggests that autophagic cell death may play a role in neuronal death after spinal cord trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 29 publications
(21 reference statements)
5
61
0
1
Order By: Relevance
“…Recently, it has been reported that autophagy has a key role in injured spinal cord tissue. 6,30,31 In this study, we report that autophagy is activated at the injury site after SCI. LC3B expression is increased, beginning at 4 h and peaking at 7 days after SCI.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, it has been reported that autophagy has a key role in injured spinal cord tissue. 6,30,31 In this study, we report that autophagy is activated at the injury site after SCI. LC3B expression is increased, beginning at 4 h and peaking at 7 days after SCI.…”
Section: Discussionmentioning
confidence: 96%
“…6,7 The protective effects of VCE against apoptotic cell death are well described in the literature. 8,9 Some studies also demonstrated associations of VCE with the expression of autophagy.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, we demonstrated that after a spinal cord contusion injury in rats, levels of LC3-II, a marker of autophagy, were elevated in neurons near the lesion epicenter. 6 Liu et al, 13 provided the time course of apoptosis after a contusion injury. By 4 h, apoptosis was detected in neurons within the lesion area, and this neuronal apoptosis peaked at 8 h. A second wave of apoptotic cells, identified as oligodendrocytes, was detected throughout the white matter at 7 days, associated with degenerating axons.…”
Section: Vce Treatment Inhibits Apoptosis and Enhances Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…injection of 30 mg/kg b.w. [13,15,23,28,41] or multiple i.v. injections within 24 h [43], or 30 mg/kg b.w.…”
Section: Introductionmentioning
confidence: 99%